Instructional media in enhancing occupational safety/health in engineering workplaces: experience versus qualification (1999)
Accidents, the world over, have brought varieties of loss with diverse consequences that made them gain the attention of ILO. This paper has not only considered the concept of and legal positions in occupational safety and health, but also the perception of instructional media as means of enhancing them in engineering workplaces. A total number of 100 workers were used for the study and the result reveals no significant difference between the qualified and less qualified workers, while significant difference existed between the experienced and less experienced. It was deduced that accident rates reduction is possible through adequate provision and utilization of instructional materials in engineering workplaces.